HOW TO THINK THEOLOGICALLY ABOUT RIGHTS. Issue 3 (25th November 2015) - Hauerwas, Stanley
Abstract: In this essay I offer a nuanced account of my critique of "rights" language. I argue that my primary concern is not to discount the usefulness of rights language in contemporary expressions of legal and moral duties. Rather my concern is with the overreliance on rights language such that it guards a society from acknowledging prior claims to a common good. Rights language has become too powerful when appeals to rights threatens to replace first-order moral descriptions in a manner that makes us less able to make the moral discriminations that we depend upon to be morally wise. Finally, I turn to Simone Weil and Rowan Williams, who both turn to the body to suggest a more constructive way for thinking about rights as attending to the body, which forces us to attend to contingency. Human contingency can help us resist abstractions that fail to properly account for and address bodily needs.